Way Through which Sharing Information Would Help in Solving Trans-border Organized Crime in Africa - Kabanda, Umar (American Scientific Research Journal for Engineering, Technology, and Sciences, 2013)
My paper will discuss way through which sharing information would help in solving Trans border organized crime in Africa with a focus on Law and implementation; As a way through which information sharing would be instituted to help in solving trans-border organized crime at regional and state level reaching a conclusion of introduction of public Private partnership at state level and efficient information sharing regional initiatives at integration level with several recommendation to ensure efficient use of information as a tool in solving trans-border organized crimes with a reference to West Africa.